Coupled poro‐mechanical tangent formulation applied to sedimentary basin modeling. (3rd November 2021) - Brüch, André; Guy, Nicolas; Lemos, Paulo Sérgio B.; Maghous, Samir
Abstract: Sedimentary basin modeling involves large space domains and time periods. Reproducing the compaction processes of the sediment material requires the constitutive model to be formulated in the framework of large irreversible strains, taking both geometric and physical nonlinearities into account. This work presents a tangent formulation for the coupled poro‐mechanical system of equations resulting from the weak form of the momentum and fluid mass balance equations. The proposed workflow is integrated in a thermo‐poro‐mechanical finite element basin simulator. At material level, purely mechanical and chemo‐mechanical deformations are respectively addressed by means of plastic and viscoplastic components in the macroscopic state equations. The accuracy and efficiency of the proposed tangent formulation are assessed through the simulation of a basin geological scenario involving gravitational compaction and tectonic shortening. Both drained and undrained behaviors of the basin rocks are simulated. The procedure has significantly improved the convergence rate and reduced the computational cost with comparison to the original formulation based on the standard poro‐elastic coefficients. In order to illustrate the potential of the basin simulator to deal with real case applications, a well model from the Neuquén basin in Argentina is also presented. The results are validated against available numerical and field data for porosity, pore‐pressure and temperature.